Taxonomic notes on some Chinese species of Neolucanus Thomson and Prismognathus Motschulsky (Coleoptera: Lucanidae) - Wan, Xia; Bartolozzi, Luca; Yang, Xingke (Zootaxa, 2007)
Two new synonyms are proposed for Chinese Lucanidae: Neolucanus montanus Kriesche, 1935 = Neolucanus aterrimus Weinreich, 1959 new synonym and Prismognathus platycephalus (Hope, 1842) = Prismognathus branczicki Nonfried, 1905 new synonym. Some observations on the abnormality of the holotype of Prismognathus klapperichi Bomans, 1989 and the similarities between this species and Prismognathus dauricus (Motschulsky, 1860) are discussed.